Apresiasi Musik Klasik Melalui Electone = Classical Music Apreciation by Means of Electone - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT The development and change in the world of art, especially music, is related to technological development. An electronic musical instrument utilizing technological development is electone, a keyboard instrument that produce various imitation sounds of acoustic instruments simultaneously alike an orchestra or a band. This thesis tried to identify tendencies found on arrangement of classical music for electone and musical appreciation fasilitated by such arrangement. The research applied textual and contextual approach. The textual approach was conducted by comparing a three scores of classical music and its arrangements for electone. To overcome constraints of electone notation system, e.g. the written text does not represent the sound it is produced, this study was supplemented by audio-visual recording of performance of three arrangements of classical repertoires for electone. Classical music appreciation was identified contextually by interviewing three electone player's playing the selected repertoires. Analysis concerning the player's appreciation was qualitatively held by finding significant relations amongst their opinions, the original scores and its arrangements, and the audio-visual recording of their playing. The research found out several tendencies on the arrangement of classical music for electone: (1) if the arrangement takes the whole composition of the classical music, it tends to keep the original characters and forms